Multi-Level Product Line Customization - Elsner, Christoph; Schwanninger, Christa; Schröder-Preikschat, Wolfgang; Lohmann, Daniel (New Trends in Software Methodologies, Tools and Techniques (SoMeT 2010), 2010)
Managing and developing a set of software products jointly using a software product line approach has achieved significant productivity and quality gain in the last decade. More and more, product lines now are becoming themselves entities that are sold and bought in the software supply chain. Customers build more specialized product lines on top of them or derive themselves the concrete products. As customers have different requirements, whole product lines now may vary depending on customer needs-they need to be customized. Current approaches going beyond the scope of one product line do not provide appropriate means for customization. They either are tailored to specific implementation techniques, only regard customization on few levels (e.g., only source code level), or imply a lot of manual effort for performing the customization. The PLiC Approach tackles this challenge by providing a generic, reusable reference architecture and methodology for implementing such customizable product lines. In the reference architecture, a product line consists of so-called product line components (PLiCs), which are flexibly recombinable slices of a formerly monolithic product line, thereby maintaining strict separation of concerns. The approach furthermore comprises a tool-supported methodology for recombination of PLiCs based on customer needs and thus minimizes manual intervention when customizing. We implemented the PLiC Approach for a complex model-driven product line, where it facilitates comprehensive customization on various levels in the models, the model transformation chain, and in the source code with reasonable effort. This gives evidence that our approach can be applied in various other contexts where the same or fewer customization levels need to be considered.
UnivIS-Import:2015-04-16:Pub.2010.tech.IMMD.IMMD4.multil
Keywords: Model-driven development; Software product line architecture; Software product line development